Фарғона водийси адир минтақалари чигирткаларининг (acridoidea) фаунаси ва экологияси (SCIENCE and SOCIETY, 2019)
According to the results of the studies, large representatives of the locust family were found in the adyr regions of the Ferghana Val- ley, of which 3 species of the family, 22 species of the genus and 29 species. In the regions where studies were conducted, 17 species were found in high adyrs, 21 species in average heights, 12 species in low adyrs and 14 interstitial balots, in river valleys. The degree of similarity of locust family species in the Adyr regions, the locust fauna of high Adyrs and in the middle heights of Adyrs, the highest similarity coefficient is 0.61. and in low adyrs, inter-adyr balots and in river valleys, the average similarity coefficient is 0.47. locust fauna of high adyrs and in medium high-altitude adyrs, the lowest coefficient of similarity is 0.33.